PENGARUH KONSENTRASI NITROGEN DAN PLANT CATALYST TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELADA (LACTUCA SATIVA L.) SECARA HIDROPONIK - Warganegara, Gorendva R.; Ginting, Yohanes Cahya; Kushendarto, Kushendarto (Jurnal Penelitian Pertanian Terapan, 2015)
Lettuce (Lactuca sativa L.) is a vegetable plant which consumption in fresh form. Color, texture, and aroma lettuce can beautify also be an ornamental dish of food. Request lettuce until now has not met its full potential, it is because there are obstacles in cultivation that influence the quality and production results. One technique that can be used in the cultivation of lettuce ie hydroponic. The purpose of this study was to: (1) To know the effect of Catalyst Plant on growth and yield of plants in hydroponic lettuce, (2) To know the effect of the concentration of nitrogen on the growth and yield of plants in hydroponic lettuce, (3) To determine the concentration of nitrogen in response to the liquid fertilizer Catalyst Plant. This study uses a randomized group design perfect (RKTS) arranged factorial (5x2) with three replications. The first factor is the nitrogen concentration of 200 ppm, 225 ppm, 250 ppm, 275 ppm, 300 ppm supplied from planting as much as 3 times a day. The second factor is the provision of liquid fertilizer Catalyst Plant (P1) and without giving liquid fertilizer (P0) with a concentration of 2 g / L of water. Interval application of liquid fertilizer once a week until harvest time. Data were analyzed by analysis of variance to investigate the influence of the treatment applied. If there are significant between the treatment continued with the separation of the middle value of Orthogonal polynomial at 5%. Of the two factors obtained 10 combined treatment with 3 replications and obtained 30 experimental units. Each experimental unit planted two plants, so that the overall use of 60 trial plants Catalyst Plant liquid fertilizer application resulted in better plant growth compared without giving liquid fertilizer. Increased nitrogen concentration of 25 ppm, the concentration of 250-300 ppm improve the growth of plant height of 0.02 cm, 0.01 cm long roots, and plant fresh weight of 0.03 grams (11:12%). There are a response to the nitrogen concentration of liquid fertilizer Catalyst Plant . Keywords: Grand Rapid lettuce, hydroponics, Catalyst Plant, the concentration of nitrogen